Problematika Film Alih Media: Dari Transformasi Hingga Kontroversi - Saidi, Acep Iwan; Puspitasari, Dyah Gayatri (LP2M ISBI Bandung, 2020)
ABSTRACTThis article contains a study of film adaptation from a literature media (novel) into audio-visual media(film). This research is a case study of Perempuan Berkalung Sorban film by Hanung Bramantyo, whichwas adapted from a novel with the same title that was written by Abidah el-Khalieqy. By combining a textanalysis method from Thomas Leittch, Mathew T. Jones’ film adaptation theory and the result of interviewto confirm the text analysis, this research produced some interesting findings. The research verified thatthe adaptation’s process does not merely focus on technical issue in media adaptation (from novel tofilm), but also focuses on another aspects that will involve the audience i.e. a fact that text and dialoguebecome references that will be appreciated by audience. As a result, there were excessive distortions anddeviations on the text that were created by the film maker caused a bias interpretation. Audiences nolonger interpreted the film as a visual text objectively. Instead, they would think about certain prejudiceagainst the film maker. In film adaptation, certain tendencies of film maker are easy to be predicted byaudience. This fact has caused film adaptation becomes controversial easily.Keywords: Media Adaptation, Transformation, Opposition, ControversyABSTRAKArtikel ini berisi kajian tentang alih media, yakni dari media verbal sastra (novel) kemedia visualfilm. Kajian ini berupa studi kasus terhadap film Perempuan Berkalung Sorban karya HanungBramantyo, yang merupakan adaptasi dari novel dengan judul sama karya Abidah el-Khalieqy.Dengan menggunakan metode gabungan, yakni analisis teks yang berdasar pada teori adaptasifilm dari Thomas Leittch, Mathew T. Jones, dan wawancara tertulis untuk mengkonfirmasianalisis teks tadi, kajian ini menemukan hal menarik, yakni alih media bukan sekedar persoalanteknis pemindahan media, melainkan juga pemindahan yang menimbulkan efek-efek tertentubagi penonton. Apresiasi penonton dilandasi kesadaran bahwa terdapat teks lain yang menjadirujukan film bersangkutan. Akibatnya, distorsi dan deviasi yang terlalu jauh yang dilakukansutradara atas teks sumber berpotensi mengakibatkan bias pemahaman. Penonton tidak lagimemaknai film sebagai teks visual secara objektif, tetapi juga dibarengi praduga-pradugatertentu terhadap sutradara. Pada genre film alih media, tendensi tertentu dari sutradara mudahdibaca penonton. Fakta ini mengakibatkan film sangat rentan menimbulkan kontroversi.Kata Kunci: alih media, transformasi, oposisi, kontroversi